PENGARUH CONTENT MARKETING DAN USER-GENERATED CONTENT INSTAGRAM TERHADAP BRAND EQUITY PADA KONSULTAN PARIWISATA DESMA CENTER - Firra Kholisha Mustika; Rahmat Ingkadijaya; Adhi Trirachmadi Mumin (Media Bina Ilmiah, 2023)
The development of technology has led to a shift in marketing trends in tourism from conventional (offline) to digital (online) channels using social media platforms. Instagram is one of the platforms that can be used to market products. Two-way communication on digital marketing on Instagram with soft selling techniques can make consumers more interested. Content marketing strategy is one of the techniques to attract consumer engagement with the aim of introducing the brand. This study aims to analyze the effect of content marketing and user-generated content Instagram on brand equity at DESMA Center tourism consultants. Using quantitative-descriptive methods with primary and secondary collection techniques. There are 3 research variables with 13 indicators in this study. The number of respondents was 100 people. Data processing techniques using Structural Equation Modeling-Partial Least Square (SEM PLS) with the help (software), by SmartPLS. After analyzing the Respondent Achievement Rate (TCR) of the three variables has a very good value with a score> 81%, content marketing variable is 85.8%, user-generated content variable is 88.2%, and the brand equity variable is 85.1%. The research results obtained are; there is an influence of content marketing variables on brand equity, there is an influence of content marketing variables on user-generated content and there is no influence of user-generated content variables on brand equity.